Mengenalkan Sertifikasi Kompetensi dan Pemeliharaan Kompetensi - Yuwono, Susatyo; Firdaus, Aprilia; Silviana, Nabiilah Dita (Universitas Muhammadiyah Surakarta, 2022)
Understanding of competence and maintaining competence is an important part of human resource development in Indonesia. Higher Education which is part of human resource development needs to ensure that students have the same understanding. The activity aims to provide an understanding of the importance of certification and competency maintenance. The activity was carried out by online method through the Zoom Room Meeting application, with 79 participants from various backgrounds. In collaboration with the Psychology Competency Test Center of Universitas Muhammadiyah Surakarta, the material presented for 60 minutes includes the understanding and elements of competence, recognition of competence, and strategies for maintaining competence. The success of the activity was assessed by measuring the understanding of competence before and after giving the material (pre-test and post-test), with the results showing an increase in the average value of pre-test and post-test although not statistically significant. The next event is recommended to use a more practical method regarding the same material.